Determinants of household demand for services: Formal versus informal sector - Izabela Styczynska (Center for Social and Economic Research (CASE), 2012)
This paper addresses the issue of household demand for services in Poland when informal sector is taken into consideration. The aim of the study is threefold: (i) to investigate the factors influencing households expenses for services, (ii) to find the determinants of households' tax strategy (choice between acquiring services on regular labour market or not), (iii) to investigate the differences between the factors that influence the expenses for formal versus informal services. Two-step Heckman selection model is used to account for the selection into buying household services. Lee's (1983) procedure is adopted to control for the selection into the particular choice of tax strategy when purchasing household services. The decision whether to buy household services and whether formally or informally is modelled as a sequential choice and estimated by bivariate probit with selection. An important novel feature of the model used is the inclusion of variables that capture social norms and personal attitudes toward tax evasion. The study concludes that factors influencing expenses for services are positively related to financial situation of households, education and age of household head. The probability of avoiding taxes is higher for lower income households, households with more than one member and for those where a positive attitude toward informal employment is expressed. The impact of determinants of expenses for formal and informal services separately is comparable. Only household structure has the opposite effect on expenses for formal services versus informal ones.
Keywords: D13; H26; J23; 330; Informal employment; Households expenditure; Services in the home; Privater Konsum; Privater Haushalt; Dienstleistung; Informelle Wirtschaft; Polen